Utilizing radar graphs in the visualization of simulation and estimation results in network meta-analysis - Seide, Svenja; Jensen, Katrin; Kieser, Meinhard (Research synthesis methods, 2021)
Traditional visualization in meta-analysis uses forest plots to illustrate the combined treatment effect, along with the respective results from primary trials. While the purpose of visualization is clear in the pairwise setting, additional treatments broaden the focus and extend the results to be illustrated in network meta-analysis.